2004
DOI: 10.1111/j.1365-2389.2004.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and solubility of Cu, Ni and Pb in contaminated soils

Abstract: A long-term incubation experiment was established to assess the solid Ð solution equilibria of (Cu 2þ ), (Pb 2þ ) and (Ni 2þ ) in soil pore water. The experiment comprised 23 soils spiked with 135, 300 and 75 mg kg À1 of Cu, Pb and Ni, respectively, added as nitrate salts in solution. Samples of soil pore water were extracted several times during the incubation period of 818 days and concentrations of Cu, Pb, Ni, dissolved organic carbon and major cations and anions were measured. Similar measurements were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 47 publications
(81 reference statements)
0
46
4
Order By: Relevance
“…NPOC concentrations also showed little variation with depth. There was not a significant correlation between Pb concentration in pore water and pH, although it was noted that Pb concentrations sharply decreased at soil pH>7 due to the greater Pb sorption with increasing pH (Tye et al, 2004). No correlation was found between Pb concentrations in pore solution and NPOC or any sorptives phases (LOI, FeO or clay).…”
Section: Solution Poolmentioning
confidence: 68%
See 1 more Smart Citation
“…NPOC concentrations also showed little variation with depth. There was not a significant correlation between Pb concentration in pore water and pH, although it was noted that Pb concentrations sharply decreased at soil pH>7 due to the greater Pb sorption with increasing pH (Tye et al, 2004). No correlation was found between Pb concentrations in pore solution and NPOC or any sorptives phases (LOI, FeO or clay).…”
Section: Solution Poolmentioning
confidence: 68%
“…Other studies have reported that decreased lability of Cd and Zn is associated with stronger adsorption, which is essentially pH-dependent (Tye et al, 2002;Young et al, 2007). Lead solubility in moderately contaminated soils is usually controlled by sorption and complexation processes rather than precipitation (McBride et al, 1997;Welp and Brümmer, 1999) is added to soils, the majority of the fixation occurs within ~300 days (Tye et al, 2004). Much of the Pb has probably been in contact with the soil for considerable periods (possibly 1000's of years) and has reached a pseudo-equilibrium with the soil properties before being eroded and re-deposited.…”
Section: E-value Vs Depthmentioning
confidence: 99%
“…Input data to WHAM 7 40 included solution pH, temperature (277 K) and solution concentrations of Na, Mg, Al, K, Ca, Fe(III), Mn, Ni, Cu, Zn, Cd, Pb, Cl -, NO 3 -, SO 4 2-, CO 3 2-, F -and PO 4 3-. Colloidal fulvic acid was also included assuming that fulvic acid contains 50% nonpurgable organic carbon (NPOC) and only 65% was active, the 45 remainder being inert with respect to ion binding 46 …”
Section: Solution Speciation and Predictive Modelling Using Wham 7 35mentioning
confidence: 99%
“…Input data to WHAM 7 40 included solution pH, temperature (277 K) and solution concentrations of Na, Mg, Al, K, Ca, Fe(III), Mn, Ni, Cu, Zn, Cd, Pb, Cl -, NO 3 -, SO 4 2-, CO 3 2-, F -and PO 4 3-. Colloidal fulvic acid was also included assuming that fulvic acid contains 50% nonpurgable organic carbon (NPOC) and only 65% was active, the 45 remainder being inert with respect to ion binding 46 . The possible existence of sub-micron FeOx and AlOx colloidal complexes was overcome by including the FeOx and AlOx precipitation option in WHAM 7 where the metals are allowed to precipitate out with a surface charge 47 .…”
mentioning
confidence: 99%
“…Examples include 71 the acidification of soils [7][8][9][10][11][12][13][14] and surface waters [15] , trace metal behaviour in soils [16][17][18][19][20][21][22] , surface 72 waters [23][24][25][26][27][28][29][30][31] and groundwaters [32] , lake sediment diagenesis [33,34] , rare earth geochemistry [35-73 37] , iron and manganese geochemistry [38][39][40][41] , radionclide geochemistry [42][43][44][45] , organic matter 74 solubility in soils [46,47] , catchment modelling [48,49] , interactions of metals with biota [50,51] , 75 ecotoxicology [52][53][54][55][56][57][58][59] and Critical Loads …”
Section: Tipping Et Al Humic Ion-binding Model Vii_revisionmentioning
confidence: 99%